Parents Assistance on Down Syndrome Children: Pastoral Counseling Perspective - Pakpahan, Gernaida Krisna R; Pantan, Frans; Salim, Muche Mona; Wiryohadi, Wiryohadi; Cahyono, Heru (Department of Guidance and Counseling, FIP, Undiksha, 2021)
Researchers aim to find out how to strengthen and assist parents with strategies for children with Down syndrome to become independent. The method used is qualitative—the procedure used for data collection by observation, interviews, and documentation. Furthermore, the data were analyzed using a data reduction model, data presentation, and verification. The resource persons for this study were ten parents with Down Syndrome children and servants of God involved in pastoral care for families with Down Syndrome children in Jakarta. The results showed that the community for parents with Down Syndrome children is essential because it provides reinforcement and support in mentoring children with down syndrome. After attending formal and informal therapy, Down syndrome children have significant developments that enable DS children to be independent. The primary model of parental assistance is holistically providing whole love and providing therapies, especially music and spiritual therapy.